2002
DOI: 10.2320/matertrans.43.537
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Gas Atomized Aluminum Alloy Powder Compact Densified by Pulsed Current Pressure Sintering Process

Abstract: A Pulsed current pressure sintering (PCPS) method was employed to sinter compacts of gas atomized Al-8%Ni-2%Mn-1%Cu-0.8%Zr-0.7%Ti-0.25%Mg alloy powder which consisted of Al-Al 3 Ni eutectic and α-Al supersaturated solid solution due to high quenching rates. Results are as follows: (1) The sintered compacts had Al 3 Ni precipitates on the boundaries of the initial Al particles. As those precipitates increased, the hardness of the compact decreased. Maximum value of hardness of the compact was HV200 and about 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Sintering occurs at these points and the interior of the powder particles is nearly unaffected and retains the microstructure formed during atomization. Spark discharge is limited to contact points where it can break up the oxide layers present at the powder particle surface and contributes thus to a very low porosity of the sintered material [ 4 ]. A further advantage of SPS is a short time of exposition to elevated temperatures which helps to limit undesirable processes like grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…Sintering occurs at these points and the interior of the powder particles is nearly unaffected and retains the microstructure formed during atomization. Spark discharge is limited to contact points where it can break up the oxide layers present at the powder particle surface and contributes thus to a very low porosity of the sintered material [ 4 ]. A further advantage of SPS is a short time of exposition to elevated temperatures which helps to limit undesirable processes like grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…First of all no differences were detected in applying the pressure using mode I or II and the data represent the samples obtained in mode II. This is very important because it has been shown [5,7] that mode II gives a stronger neck growth and higher ductility compared to mode I. On the sintered parts it was difficult to perform reliable microhardness measurements due to the low load.…”
Section: Resultsmentioning
confidence: 99%
“…11 Other authors showed that using this kind of schedules minimises the quantity of gas entrapped into the powder returning in higher sustainable plasticity. 12…”
Section: Effect Of Pressurementioning
confidence: 99%